Dual-structure-breaking electrolyte enables practical cadmium-metal battery - Cui, Yang-Feng; Song, Hao-Bin; Yao, Jing-Jing; Hao, Qi; Li, Xue-Liang; Li, Yi-Fan; Guo, Bin-Bin; Zhu, Yun-Hai; Yang, Hui Ying (Nature communications, 2025)
High-energy aqueous metal batteries are promising candidates for the next-generation energy storage systems but face critical challenges of dendrite and corrosion in metal negative electrodes. To address these issues, we report an aqueous cadmium-metal battery employing a fast-kinetics structure-breaking electrolyte composed of CdCl 2 and NH 4 Cl. The addition of NH 4 Cl induces the formation of dual structure breakers, NH 4 + and tetrachlorocomplex ([CdCl 4 ] 2– ), which facilitate fast charge transfer kinetics in aqueous cadmium-metal batteries and endow dendrite-free/corrosion-resistant capabilities to Cd negative electrodes. This tailored electrolyte realizes a convincing Coulombic efficiency (99.93%) for Cd plating/stripping behavior at a high Cd utilization of 55%, making it suitable for practical applications. Moreover, the fast-kinetics aqueous cadmium-metal batteries exhibit remarkable compatibility with diverse types of positive electrodes, including conversion-, coordination-, intercalation- and capacitance-type, offering enhanced rate performance and durable rechargeable stability. These results establish a robust and scalable aqueous battery design for sustainable energy storage systems. High-energy aqueous metal batteries are promising candidates for the next-generation energy storage systems yet face detrimental parasitic reactions. Here, authors develop a durable cadmium-metal battery employing a fast-kinetics dual-structure-breaking electrolyte.